Waterborne Acrylic-Casein Nanoparticles. Nucleation and Grafting - Picchio, Matías Luis (2014)
Hybrid nanoparticles containing proteins have a technological interest because they attempt to achieve improved properties with respect to the single materials by chemically linking both components. In this article, the batch emulsion polymerization of methyl methacrylate in the presence of varied concentration of casein and tert-butyl hydroperoxide as initiator was investigated. A detailed characterization of the molecular microstructure and morphology of the hybrid nanoparticles allowed the identiﬁcation of two competitive particle formation mechanisms. Compatibilized nanoparticles were produced at the beginning of the polymerization, while uncompatibilized particles could be generated by a second way of nucleation, which is promoted by the ungrafted protein and depends on its concentration.